2006
DOI: 10.1002/pola.21324
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of poly(ethylene oxide‐co‐ethylene carbonate) macromonomers and their use in the preparation of crosslinked polymer electrolytes

Abstract: Methacrylate‐functionalized poly(ethylene oxide‐co‐ethylene carbonate) macromonomers were prepared in two steps by the anionic ring‐opening polymerization of ethylene carbonate at 180 °C, with potassium methoxide as the initiator, followed by the reaction of the terminal hydroxyl groups of the polymers with methacryloyl chloride. The molecular weight of the polymer went through a maximum after approximately 45 min of polymerization, and the content of ethylene carbonate units in the polymer decreased with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…Finally, a weaker process is observed in the 400–500°C region which is attributed to the degradation of the polymeric backbone (Process 3). The results are in agreement with those reported in the literature 6, 24, 25…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Finally, a weaker process is observed in the 400–500°C region which is attributed to the degradation of the polymeric backbone (Process 3). The results are in agreement with those reported in the literature 6, 24, 25…”
Section: Resultssupporting
confidence: 93%
“…In response to this challenge, intense research has focused on the design of new materials having improved transport properties compared to the commercial membranes presently used as electrolytes in fuel cells, such as Nafion 5. The aim of this work is to prepare materials with structures that combine high water contents to facilitate and promote proton conductivity with low methanol permeability to avoid fuel crossover 6. To achieve this goal in a rational manner, we must both understand the morphology of the membrane, and learn how to control several parameters such as the interactions between functional groups, the organization of absorbed water, the extent of hydrogen bonding, and the chemical environment of the proton conducting groups.…”
Section: Introductionmentioning
confidence: 99%
“…It clearly shows that the proton d (at δ = 4.27) is related -20 and + 20 ° C was observed. [ 30 ] This is understandable because either EC or EO segments are so short that they can not fold or pack in ordered crystalline domains. DSC results also show that the copolymer has only one glass transition temperature ( T g ) around -42 ° C, further indicating that the copolymer chain is amorphous.…”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30][31] Usually, the polymerization of EC is accompanied by decarboxylation, which most likely involves metal carbonate species formation due to ring opening via CAO bond cleavage. 1,21,32 The absence of a signal between 3.10 and 3.30 ppm indicates that the polymers obtained with Ln(DBMP) 3 are free of ether units developed from carbon dioxide elimination of EC or DTC, and this indicates that these lanthanide complexes are efficient catalysts for the synthesis of aliphatic polycarbonates at reasonably low temperatures. 28,29 The SEC measurements showed that poly(DTC-co-EC)s with high molecular weights as well as reasonably narrow molecular weight distributions were successfully prepared with La(DBMP) 3 .…”
Section: Random Copolymerization Of Dtc and Ecmentioning
confidence: 97%